The Effect of Prodigy towards Junior High School Students' Grammar Competence - Aisya Setiawan (Retain: Journal of Research in English Language Teaching, 2025)
Abstract The study aimed to know whether Prodigy, an English digital learning media, has significant effect towards junior high school students’ grammar competence. Prodigy is a digital learning application which has just launched its English learning feature in 2022. Design of the study was quantitative with experimental research method. Subject of the study were the eighth graders of junior high school. There were two classes, in which each class had 35 students. The first class was the experimental group and the second class was the control group. The study was conducted in a public junior high school in East Java. Data of the study was gathered using instruments, Pre-Test and Post-Test. The result of the study showed that the implementation of Prodigy as a digital English learning media has significant effect towards students’ grammar competence. The researcher analysed the pre-test score. It showed that there is no significant difference between students of both classes and they had equal ability in grammar competence. Furthermore, in order to know the significant difference towards students’ grammar competence after the implementation of Prodigy, a treatment was given to the experimental group. The treatment was conducted in five meetings. Students played Prodigy with the guidance of the researcher. After the treatment was completed, post-test was administered to both groups. Ultimately, post-test score was analysed. Based on the non-parametric guide, the result was considered to be statistically significant. In conclusion, Prodigy, as an English digital learning media, was able to help students to improve students’ grammar competence, especially present and past tense. Keywords: Grammar, Digital Learning Media, Prodigy, Teaching and Learning